Анатомо-топографічні та гістологічні аспекти підшлункової залози одногорбого верблюда - Рахмун, Джаллал Еддін; Rahmoun, D. E.; Лєщова, Марина Олексіївна; Lieshchova, M. O.; Lieshchova, M. А.; Lieshchova, M.; Lieshchova, Maryna; Lieshchova, Marina (Дніпровський ДАЕУ, 2022)
Наведена інформація щодо особливостей макроанатомії, топографії, морфометричних параметрів і гістологічної будови підшлункової залози одногорбого верблюда із південно-східного регіону Алжира. The article presents information on the features of the macroanatomy, topography, morphometric parameters and histological structure of the pancreas of a dromedary from the southeastern region of Algeria.
The anatomo-topographical and histological aspects of the pancreas of the dromedary
Лєщова Марина Олексіївна http://orcid.org/0000-0002-4251-4152
Keywords: підшлункова залоза; pancreas; Camelus dromedarius; Camelus dromedarius; панкреатичні острівці; islets of Langerhans